INTEGRASI IMAN & ISTIQOMAH DALAM MEMBENTUK MANUSIA PARIPURNA - Ahmad Azaim Ibrahimy (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
Muslim life lived through the phases a very long and winding process with the task as the creation of Allah, including many things that are urgent for always be considered in themselves in relation to keeping all the obligations of the syari'at. The strength of Aqidah is be decisive in all activities servitude and purification, in other to be a Muslim individuals who getting a glory by Allah SWT